Toxic Work Environment and Psychological Distress in Indonesian Multisector Companies: A Narrative Review Through the Lens of Psychological Safety Theory (2024–2026) - Anang Setiawan (Abadi Institute, 2026)
Toxic work environments remain a persistent organizational problem in Indonesia, particularly in sectors characterized by high emotional labor, close supervision, heavy customer interaction, and strong performance pressure. This narrative review examines whether the relationship between toxic work environment and psychological distress is a sufficiently recurrent phenomenon in Indonesian multisector organizations during 2024–2026, and whether Psychological Safety Theory provides an adequate explanation for that relationship. Using a purposive narrative review approach, the article synthesizes open-access evidence from Indonesian empirical studies and reviews published in 2024–2026 across contact center, manufacturing, education, and mixed-sector organizational settings. The reviewed literature consistently depicts toxic work environments as settings marked by poor communication, lack of support, interpersonal conflict, bullying, discrimination, unfairness, and psychologically unsafe leadership. Across the reviewed studies, toxic work conditions are associated with elevated work stress, anxiety, emotional exhaustion, depressive symptoms, reduced performance, and withdrawal cognition. The review finds that the toxic environment–distress link appears repeatedly across sectors rather than as an isolated sector-specific anomaly. Psychological Safety Theory explains this pattern by emphasizing that employees who do not feel safe to speak up, admit mistakes, ask for help, or express concerns allocate more cognitive and emotional energy to self-protection than to task performance. In such contexts, informal social control mechanisms—such as fear, blame, silence, and exclusion—amplify distress. The review concludes that, in Indonesia, Psychological Safety Theory remains a useful and empirically plausible lens for explaining how toxic work environments contribute to psychological distress, although current evidence is still fragmented and often uses distress proxies such as work stress, anxiety, and emotional exhaustion. The article identifies research gaps and proposes directions for future empirical studies using multi-sector samples, longitudinal designs, and direct measurement of psychological safety and psychological distress.